2016
DOI: 10.1093/ndt/gfw297
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resistance exercise and oral nutritional supplementation during hemodialysis on indicators of nutritional status and quality of life

Abstract: Oral nutritional supplementation during HD improves NS. The addition of RE during HD does not seem to augment the acute anabolic effects of intradialytic ONS on NS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 48 publications
6
76
0
3
Order By: Relevance
“…In a retrospective evaluation of ONS in HD patients, authors observed a reduction in days of HD treatment missed and mortality risk, despite a lack of significant improvement in serum albumin [47]. Nutrition intake and anthropometric measures improved, and PEW was reduced in a randomized clinical trial of ONS in HD patients [48]. Increasing ONS use in HD patients with malnutrition risk should be further investigated to establish their inclusion as part of evidence-based patient care, as has been proposed by the ISRNM [49].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective evaluation of ONS in HD patients, authors observed a reduction in days of HD treatment missed and mortality risk, despite a lack of significant improvement in serum albumin [47]. Nutrition intake and anthropometric measures improved, and PEW was reduced in a randomized clinical trial of ONS in HD patients [48]. Increasing ONS use in HD patients with malnutrition risk should be further investigated to establish their inclusion as part of evidence-based patient care, as has been proposed by the ISRNM [49].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the type of ION used, it should be noted that studies evaluating the use of both food and oral supplements have not shown one to be better than the other. Nutritional markers other than albumin and nitrogen balance have not been studied, including hand grip strength or physical functionality 31 or bioelectrical impedance. The present study found that HCP mostly perceives ION as a good opportunity to improve the QoL of HD patients, so it is important to evaluate this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle mass increased through enteral nutrition therapy based on the results of an RCT comparing the effects of enteral nutritional supplementation only against leg muscle strength training plus enteral nutrition therapy in dialysis patients. No additional increases in skeletal muscle mass were determined to have resulted from the addition of leg strength training . Although most studies in this area have been small‐scale, exercise + nutritional supplementation could possibly help prevent sarcopenia in patients with CKD.…”
Section: Cq3: Can Interventions For Non‐communicable Diseases Preventmentioning
confidence: 99%